Bacteriophage T4 gene 32 protein: Insights into its interaction with ssDNA, binding cooperativity, and conformational change - Jules Guei; Michael P. Chapman; Paul N. Brothers; Shital Desai; Richard L. Karpel (PLoS ONE, 2026)
The single-stranded DNA binding protein of bacteriophage T4, gp32, has important roles in replication, recombination, and repair. gp32 possesses three domains: the central (core) domain which contains the binding trough for single-stranded DNA, the N-terminal domain, which interacts with the core domain of an adjacent ssDNA-bound protein, bringing about binding cooperativity, and the C-terminal domain, which interacts with other proteins involved in replication, recombination, and repair. The essential residues within the N-domain for the association with the adjacent DNA bound gp32, Lys-Arg-Lys-Ser-Thr, the “LAST Motif” , is almost identical to the ssDNA-interactive residues within the core domain binding trough, and was the basis of a model in which a “closed” ⇄ “open” conformational change within core domain controls DNA binding. In this study, we show that alteration of the core domain LAST sequence , while maintaining its composition , can have an effect on the binding parameters, and may be the result of a shift in the closed-open equilibrium. Additionally, utilizing a gp32 truncated at residue 227, as well as amino acid substituted variants, we have further localized the residues within the core domain responsible for the protein-protein association leading to cooperative ssDNA binding. Truncation leads to an increase in the non-cooperative affinity for single-stranded nucleic acids, which can be explained by the absence of a closed conformation in this variant. The truncated protein forms a tight complex with core domain on a 12-residue oligonucleotide, a potential candidate for further structural study.